Assessment of the inhibition potential of Licochalcone A against human UDP-glucuronosyltransferases. (April 2016) - Xin, Hong; Qi, Xiao-Yi; Wu, Jing-Jing; Wang, Xin-Xin; Li, Yan; Hong, James Y.; He, Wei; Xu, Wei; Ge, Guang-Bo; Yang, Ling
Abstract: Licochalcone A (LCA) is a major bioactive compound in Licorice, a widely used herbal medicine. In this study, the inhibitory effects of LCA against human UDP-glucuronosyltransferases (UGTs) and LCA associated herb-drug interactions were systematically investigated. Our results demonstrated that LCA displayed broad-spectrum inhibition against human UGTs. LCA exhibited strong inhibitory effects against UGT1A1, 1A3, 1A4, 1A6, 1A7, 1A9, and 2B7 (both IC50 and K i values lower than 5 μM), while showing moderate inhibitory effects against UGT1A8, 1A10, 2B4, 2B15, and 2B17. The inhibitory effects of LCA against two major UGTs, including UGT1A1 and 1A9, were further investigated in human liver microsomes (HLMs), where the potential risks of LCA via inhibition of UGT1A1 and 1A9 were predicted by combining the in vitro inhibitory data and physiological data. The results from this study also showed that several LCA-containing products were able to increase the area under the curve (AUC) of the substrates that were predominantly metabolized by UGT1A1 or 1A9. These findings together demonstrate that LCA has a potent and broad-spectrum inhibitory effect against most human UGTs and thus suggest that much caution should be exercised when high-dose LCA is co-administered with UGT substrates. Highlights: Licochalcone A (LCA) displays broad-spectrum inhibition against human UGTs. LCA displays strong inhibitory effects against UGT1A1, 1A3, 1A4, 1A6, 1A7, 1A9, and 2B7. LCA displays potent inhibitory effects against UGT1A1 and 1A9 in human liver microsomes. The potential risks of LCA via inhibition of UGT1A1 and 1A9 were predicted for the first time.